Belief in the Naga in Buddhism - Phrakhru Pairojñānasophon; Donkamonkan , Tanakorn (Journal of Graduate Saket Review, 2024)
The Naga is the origin of the beast type, but they are special because they are non-human. Able to take the form of a human being, there are 4 clans: Virupaksa, Erapatha, Chapayaputra, and Kanhagotamaka. They live in water sources, ponds, forests and trees, termite mounds, mountains, and the Naga world or the heavens of the Jatumahārajikā. The kamma that causes one to become a Naga has both good kamma and bad kamma. The difference is that merit causes one to be born as a Nagaraja. Have divine treasures similar to those of angels The role of the Naga that appears in Buddhist scriptures includes protecting and helping those who do good. practicing good deeds He is a person who has wrong opinions, is cruel, and hurts others and is a performance device for snake charmers while maintaining the precepts of the temple. The influence of the belief in the Naga in Buddhism on Thai society includes the tradition of ordination. Traditional bathing, art, tourism and the inspiration of good fortune.